2015
DOI: 10.1186/s12862-015-0396-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of substrate recognition sites (SRSs) in cytochromes P450 from Apiaceae exemplified by the CYP71AJ subfamily

Abstract: BackgroundLarge proliferations of cytochrome P450 encoding genes resulting from gene duplications can be termed as ‘blooms’, providing genetic material for the genesis and evolution of biosynthetic pathways. Furanocoumarins are allelochemicals produced by many of the species in Apiaceaous plants belonging to the Apioideae subfamily of Apiaceae and have been described as being involved in the defence reaction against phytophageous insects.ResultsA bloom in the cytochromes P450 CYP71AJ subfamily has been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
(68 reference statements)
1
45
0
Order By: Relevance
“…However, a general tendency towards loss of activity was observed for most of the substitutions in the binding pocket with the three different tested fatty acids, suggesting a negative influence of mutagenesis on the substrate specificity and on the enzyme activity, although the selectivity was maintained. This has previously also been shown with six mammalian CYP subfamilies, among other studies, that reported significant impacts of the alteration of amino acids close to the prosthetic group or residues located at the entrance of the binding pocket on the substrate specificity and regioselectivity involved in substrate recognition . Our results suggest that with high selectivity towards fatty acids the binding pocket is already well optimized, and any changes probably only disturbed the favorable binding of the substrates.…”
Section: Discussionsupporting
confidence: 88%
“…However, a general tendency towards loss of activity was observed for most of the substitutions in the binding pocket with the three different tested fatty acids, suggesting a negative influence of mutagenesis on the substrate specificity and on the enzyme activity, although the selectivity was maintained. This has previously also been shown with six mammalian CYP subfamilies, among other studies, that reported significant impacts of the alteration of amino acids close to the prosthetic group or residues located at the entrance of the binding pocket on the substrate specificity and regioselectivity involved in substrate recognition . Our results suggest that with high selectivity towards fatty acids the binding pocket is already well optimized, and any changes probably only disturbed the favorable binding of the substrates.…”
Section: Discussionsupporting
confidence: 88%
“…Although the phylogeny only included P450s related to sesquiterpenoid metabolism, the sequences are from most families and subfamilies in the CYP71 clade. This shows that phylogenetic analyses are not useful to predict the specific functionality of P450s, as shown previously (Dueholm et al, 2015). The analyses merely serve to indicate the range of enzymes that have to be examined biochemically: in this case, 18 sequences.…”
Section: Phylogenymentioning
confidence: 77%
“…Through the transient coexpression in Nicotiana benthamiana of TgTPS2 and TgCYP76AE2, epikunzeaol is converted to epidihydrocostunolide, a likely precursor for more complex sesquiterpenoid lactones including thapsigargin. Within the Apiaceae, only P450s involved in the biosynthesis of the phenylpropanoid coumarin have been described (Larbat et al, 2007(Larbat et al, , 2009Drew et al, 2013;Dueholm et al, 2015). This work presents the functional characterization of the first sesquiterpene-specific P450 found in the Apiaceae.…”
mentioning
confidence: 97%
“…So far, we cannot exclude the possibility that the genes involved in the synthesis of the downstream furanocoumarin derivatives might be physically located at a different position from the first two loci identified in this work (Figure ) or even not grouped but spread all over the genome. We intend to investigate this matter further by: (i) screening other BAC clones using new probes, such as PsPT2 , another gene involved in the synthesis of osthenol (Munakata et al ., ) and also with other identified P450 genes (Dueholm et al ., ); and (ii) identifying and sequencing the clones surrounding the already identified BAC sequences.…”
Section: Discussionmentioning
confidence: 97%